The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1590/s0100-06832013000600027
|View full text |Cite
|
Sign up to set email alerts
|

Sugarcane trash management assessed by the interaction of yield with soil properties

Abstract: SUMMARYCurrently, sugarcane plays an important global role, particularly with a view to alternative energy sources. Thus, in a sugarcane field of the mill Vale do Paraná S/A Álcool e Açúcar, Rubineia, São Paulo State, managed under two green cane harvest systems (cane trash left on and cane trash removed from the soil), Pearson and spatial correlations between the sugarcane yield (variety RB855035 in the third cut) and soil physical and chemical properties were studied to identify the property best correlated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
0
4
0
1
Order By: Relevance
“…These results are supported by Franco et al (2015), who reported reduction of SOC in deeper layers in these same sugarcane sites. Dalchiavon et al (2013) also verified that maintenance of sugarcane straw on the soil surface increases SOC stocks, decreases bulk density and soil resistance to penetration, and improves sugarcane yield.…”
Section: Thickness Of the Soil Layers Identified By Vessmentioning
confidence: 56%
See 1 more Smart Citation
“…These results are supported by Franco et al (2015), who reported reduction of SOC in deeper layers in these same sugarcane sites. Dalchiavon et al (2013) also verified that maintenance of sugarcane straw on the soil surface increases SOC stocks, decreases bulk density and soil resistance to penetration, and improves sugarcane yield.…”
Section: Thickness Of the Soil Layers Identified By Vessmentioning
confidence: 56%
“…Adoption of harvesting without prior burning (e.g., Cerri et al, 2011), minimum tillage and maintaining straw on the soil surface (e.g., Dalchiavon et al, 2013;Segnini et al, 2013) could increase SOC and improve soil structure. Protocols that aim to have machinery enter fields under soil moisture that are less favorable to compaction in conjunction with controlled traffic strategies should also be encouraged to keep soil structure favorable for sustainable sugarcane production.…”
Section: Thickness Of the Soil Layers Identified By Vessmentioning
confidence: 99%
“…Tanaman pupuk hijau ditebang setelah berumur sekitar 2 bulan dan biomassanya dikembalikan ke lahan. Pengembalian residu tanaman ke lahan dapat meningkatkan bahan organik tanah (Dalchiavon et al 2013;Suma dan Savitha 2015), memperkaya keragaman arthropoda (Doube dan Schmidt 1998;Straalen 1998), memperbaiki kinerja mikroba tanah (Roper dan Ophel-Keller 1998;Sparling 1998), meningkatkan keragaman hayati tanah (Lio et al 2014), meningkatkan aktivitas predator (Kingstone et al 2007), dan memperbaiki kualitas tanah dan produksi tebu (Muñoz-Arboleda dan Quintero-Duran 2009).…”
Section: Pengelolaan Lahanunclassified
“…These results are supported by , who reported reduction of SOC in deeper layers in these same sugarcane sites. Dalchiavon et al (2013) also verified that maintenance of sugarcane straw on the soil surface increases SOC stocks, decreases bulk density and soil resistance to penetration, and improves sugarcane yield.…”
Section: -----------------------------------Lat_21s -----------------mentioning
confidence: 56%
“…On the other hand, long-term (>20 years) sugarcane production led to important SOC losses at Lat_23S. This SOC depletions can be associated to several causes, such as soil tillage performed for planting, fertilization and sugarcane reformation , long period of time (~10 years) with burning sugarcane harvesting system (CERRI et al, 2011;BORDONAL;FIGUEIREDO;LA SCALA JR, 2012;BRANDANI et al, 2015) and the recent crop residue removal for electricity production (CARVALHO et al, 2013). At Lat_17S were observed higher SOC and TN content under sugarcane than pasture.…”
Section: Land-use Change Effects On Soil Organic Carbon and Total Nitmentioning
confidence: 99%